From Symptoms to Diagnosis: Informing Health Promotion Strategies for Undiagnosed Diabetes Mellitus - Mahendro Prasetyo Kusumo (FORIKES, 2026)
Diabetes mellitus remains a major global health concern, with a substantial proportion of cases remaining undiagnosed. Delayed detection is particularly problematic in countries with high disease burden, where individuals often present only after complications have developed. This study aimed to identify patient-recognizable “warning” indicators observed prior to formal diagnosis to inform health promotion and opportunistic screening strategies. This study used a qualitative case study approach, symptom experiences among previously undiagnosed individuals in Sleman, Yogyakarta, were explored and analyzed. The findings indicated that hypertension, neuropathic complaints (numbness and tingling), excessive daytime sleepiness, and persistent fatigue commonly preceded diagnosis. These manifestations function as pragmatic screening prompts when interpreted alongside established metabolic risk factors. In conclusion, diagnostic delay is effectively reduced by integrating symptom awareness into risk-based screening and structured referral pathways. Formalizing everyday symptom experiences as systematic entry points into healthcare services is essential to improve early detection for undiagnosed diabetes mellitus.Keywords: diabetes mellitus prevention; health promotion; undiagnosed; screening